Symposion Krastal : Steine - Bilder - Objekte - Photos. (Wien : Wiener Secession, 1988)
Eder, Otto ; Bär, Peter ; Beuchel, Stefan ; Böhm, Hella ; Centmayer, Markus ; Clay, James ; Eiag, Tim ; Yamaya, Keiji ; Kienast, Ignaz ; Kuch, Roland ; Laich, Angela ; Machhammer, Helmut ; Maekawa, Yoshiharu ; Meier, Paul Louis ; Perz, Johannes Peter ; Pleschberger, Wilhelm ; Ranacher, Peter ; Schellander, Meina ; Steixner, Pia ; Sukenari, Masanori ; Stütz-Mentzel, Hannah ; Wachter, Brigitte ; Wiesauer-Reiterer, Heliane
Symposion Krastal : Steine - Bilder - Objekte - Photos, Wiener Secession, Wien, 8.9.1988 bis 10.10.1988
Duits
kunstcatalogus